The readability level of the 9th grade new mathematics course book - Mansour, Othman N.; Al-Rashdan, Aziza G. (Opción, 1970)
The current study aimed to identify the readability level of the 9th-grade new mathmatics course book and its relation to mathematical thinking in the Kingdom of Saudi Arabia. The study sample consisted of two categories: the first was the sample of 300-female students, and the second was the lesson-based sample consisting of (10) lessons from the mathematics book. The results of the study showed that the average readability of the 9th-grade new mathematics course book was (37%); that is, it falls in the frustration level, where the average readability of the first unit was (67.2%).